Histopathological changes in gallbladder mucosa associated with cholelithiasis - R Baidya; B Sigdel; NL Baidya (Association of Clinical Pathologists of Nepal, 2012)
Background: Gallstone is a very common gastrointestinal disorder. It is known to produce histopathological changes in the gallbladder. It is also one of the predisposing factors for the development of cancer of gallbladder. Materials and Methods: This was a retrospective study carried out in the Department of Histopathology, B and B Hospital during a period of 1 year from April 2010 to May 2011. The study included 396 cases of cholecystectomy specimens. Results: On gross examination, outer gallbladder surface was congested in 116 patients (28%), wall thickness was increased in 181 (45.7%) and mucosal abnormalities were present in 126 (31.6%) patients. At microscopy, epithelial hyperplasia was observed in 183 (46.2%), intestinal metaplasia in 112 (28.2%), dysplasia in 5 (1.3%) and cholesterolosis in 56 (14%) patients. Conclusion: The pathological changes of the gallbladder epithelium may play an important role in the process of gallstone formation. DOI: http://dx.doi.org/10.3126/jpn.v2i3.6027 JPN 2012; 2(3): 224-225